Pengaruh Terapi Murottal Al-Qur’an Terhadap Nyeri Post Operasi di Rumah Sakit Umum Daerah Syekh Yusuf - Zulfikar Tahir; Mohamad Zulfadhly Majid; Rivgi Afandy Ramadhan; Hilmi Khaula W (Universitas Muhammadiyah Surabaya, 2026)
Postoperative pain is a common problem that can slow down patient recovery. Non-pharmacological approaches such as Murottal Al-Qur’an therapy have the potential to help reduce pain intensity. This study aimed to determine the effect of Murottal Al-Qur’an therapy on pain among postoperative patients under general anesthesia. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted on 76 postoperative patients at the Syekh Yusuf Regional General Hospital, Gowa Regency. Respondents were divided into an intervention group (listening to Murottal for 15 minutes) and a control group (no intervention). Pain intensity was measured using the Visual Analogue Scale (VAS). Data were analyzed using the Wilcoxon Signed Rank test and the Mann-Whitney test. Results The intervention group showed a significant decrease in pain intensity (p=0.001). The control group also experienced a decrease, but to a lesser extent (p=0.031). Between-group comparisons indicated a significant difference in the post-test results (p=0.010). Conclusion: Murottal Al-Qur’an therapy was associated with a reduction in postoperative pain intensity and may serve as a useful non-pharmacological adjunct therapy.